2015
DOI: 10.1039/c5ee00192g
|View full text |Cite
|
Sign up to set email alerts
|

CO2-free electric power circulation via direct charge and discharge using the glycolic acid/oxalic acid redox couple

Abstract: The establishment of an efficient electric power distribution method is the key to realising a sustainable society driven by renewableenergy-based electricity, such as solar photovoltaics, wind turbine, and wave electricity, in view of supply instability. Here, we demonstrate an electric power circulation method that does not emit CO 2 and is based on the glycolic acid (GC)/oxalic acid (OX) redox couple.Direct electric power storage in GC ensures considerably high energy density storage and good transportabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 48 publications
4
51
0
Order By: Relevance
“…Therefore, the suppression of hydrogen evolution reaction (HER) over a TiO 2 electrode is critically important to achieve a high Faradaic efficiency for OX reduction, which has been discussed in our previous report. 33 The TiO 2 electrode used in this work also exhibited high activities for OX reduction but low HER activities under the acidic conditions, as reported in Nature Materials. 53 Based on these results, we succeeded in the first production of an alcoholic compound, GC, from a carboxylic acid, OX, via water oxidation using light energy through an electrochemical reaction system.…”
Section: supporting
confidence: 68%
“…Therefore, the suppression of hydrogen evolution reaction (HER) over a TiO 2 electrode is critically important to achieve a high Faradaic efficiency for OX reduction, which has been discussed in our previous report. 33 The TiO 2 electrode used in this work also exhibited high activities for OX reduction but low HER activities under the acidic conditions, as reported in Nature Materials. 53 Based on these results, we succeeded in the first production of an alcoholic compound, GC, from a carboxylic acid, OX, via water oxidation using light energy through an electrochemical reaction system.…”
Section: supporting
confidence: 68%
“…Figure 4(b) indicates that the amount of hydrogen is considerably enhanced by the inclusion of TiO 2 -II grains and the best electrocatalytic activity for hydrogen evolution is achieved on the sample with 18 wt% TiO 2 -II, whereas the conversion of oxalic acid on the three TiO 2 catalysts seems almost similar. Considering that the energy position of conduction band bottom predominantly influences the electrocatalytic oxalic acid conversion [23][24][25], the observed activities on TiO 2 catalysts for oxalic acid conversion are plausible because the conduction band energy levels are reasonably the same for the three samples. Taken altogether, it is concluded that the presence of some amounts of TiO 2 -II as the second phase in the anatase matrix can improve the electrocatalytic activity for hydrogen evolution, but the best fraction of TiO 2 -II phase for electrocatalytic activity still needs to be optimized in future studies.…”
mentioning
confidence: 82%
“…It should be noted that the group of authors recently reported the electrochemical hydrogenation of oxalic acid (divalent carboxylic acid) to produce glycolic acid (monovalent alcoholic compound) and found that the catalytic activity on TiO 2 considerably depends on the crystal structure, i.e. anatase exhibits extremely high reducibility for oxalic acid but rutile does not [23,24]. The difference in catalytic activity was attributed to the reducibility of electrons introduced from electrode to the conduction band bottom of TiO 2 , i.e.…”
mentioning
confidence: 99%
“…The functional group transformation (FGT) and subsequent reduction of CAs hence represent an important research subject to furnish alcohols for platform/fine chemicals 111 , biofuels 1113 , and electric power-storage materials 14 . Among those FGTs, the catalytic C–H bond functionalization of CAs 1517 , followed by hydrogenation 1823 , could potentially widen the diversity of alcohols thus available.…”
Section: Introductionmentioning
confidence: 99%